The use of TIC’s as a managing tool for traceability in the food industry - Pinto, D. B. (2006)
Food safety has become an important food quality attribute. Both food industry and authorities need to be able to trace back and to authenticate food products and raw materials used for food production to comply with legislation and to meet the food safety and food quality requirements. PaniGest is a user-friendly computer package designed to manage traceability and help in the quality control and production improvement. This application was developed in Visual Basic language over an SQL database and its main features are: to register quality control parameters of raw materials, in-course products and final products; to manage reception, production and expedition orders; to analyse production costs, productivity, raw materials and products’ consumptions; to trace products during the food chain. It runs on a personal computer over Windows 95/98 or Windows 2000/XP operating system. The program also uses common Internet Browsers to make information available to users.